Tracking dispersal : auction sales from the Yuanmingyuan loot in Paris in the 1860s - Howald, Christine (Journal for art market studies, 2018)
During the Second Opium War (1856-1860), British and French troops fought to expand their privileges in China. The war ended in Beijing in October 1860 with the looting and burning of the Yuanmingyuan, one of the official seats of government of the Chinese Emperor to the northwest of the Chinese capital. Thousands of these objects - figures up to over a million have been suggested - were brought to Europe and are today in Western museums and private collections. Little is known about the quantity of objects that reached Europe, about the market mechanisms in the West, the collectors that purchased the artefacts from the Summer Palace, as well as the paths taken by the objects in the years after 1860: which objects arrived in Europe? In whose hands were they at what time? When did they change hands? Where are they today? While it is difficult to trace the marketing of the artefacts sold through dealers - due to the scarcity of available archives -, public auction sales are easier to access. This paper provides a systematic review of all Parisian sales between 1861 and 1869 in which artefacts from the Imperial Summer Palace were sold. The corresponding catalogues were matched with the minutes of the sales - a specifically French source providing unique information on sellers, buyers and prices of the sold objects. The complete dataset with the description of artefacts and protagonists is available online.